Tales from Spandau : Nazi criminals and the Cold War - Goda, Norman J. W. 1961- (Cambridge Univ. Press, 2007)
Sentenced to long prison terms at the Trial of the Major War Criminals at Nuremberg, seven of Adolf Hitler's closest associates - Rudolf Hess, Albert Speer, Karl Dönitz, Erich Raeder, Walther Funk, Konstantin von Neurath, and Baldur von Schirach - were to have become forgotten men at Berlin's Spandau Prison. Instead they became the focus of a bitter four decade tug-of-war between the Soviet Union and the Western Allies - a dispute on the fault line of the Cold War itself which drew in heads-of-state, military strategists, powerful businessmen, vocal church leaders, old-world aristocrats, international spies, and neo-Nazis. Drawing on long-secret records from four countries, Norman J. W. Goda provides an exciting new perspective on the terrifying shadow thrown by Nazi Germany on the Cold War years, and how that shadow helped to influence the Cold War itself.